2020
DOI: 10.1021/acs.langmuir.0c00046
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal-Mediated DNA Adsorption on Polydopamine Nanoparticles

Abstract: Polydopamine (PDA) is a widely used universal coating for a broad range of materials. Interfacing PDA with various biomolecules, such as DNA, is critical for applications such as sensing, intracellular delivery, and material fabrication. Because of the negative surface charge of PDA at neutral pH, electrostatic repulsion exists between PDA and DNA. In previous studies, modified DNA or low pH was used to overcome this repulsion for DNA adsorption. More recently, divalent Ca2+ was found to bridge DNA and PDA. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 47 publications
2
36
0
Order By: Relevance
“…It is common to use Tris buffer at pH 8.5, [50][51][52][53][54] or to directly add NaOH to an aqueous solution of dopamine. [47,55] Interestingly, some works claimed to have synthesized PDA at lower pH, but extra oxidizing agents were needed. Wei et al showed that by adding ammonium persulfate and sodium periodate, polymerization can occur at neutral and even acidic pH.…”
Section: Effect Of Phmentioning
confidence: 99%
See 4 more Smart Citations
“…It is common to use Tris buffer at pH 8.5, [50][51][52][53][54] or to directly add NaOH to an aqueous solution of dopamine. [47,55] Interestingly, some works claimed to have synthesized PDA at lower pH, but extra oxidizing agents were needed. Wei et al showed that by adding ammonium persulfate and sodium periodate, polymerization can occur at neutral and even acidic pH.…”
Section: Effect Of Phmentioning
confidence: 99%
“…PDA is a zwitterionic material as it contains both amine groups and phenolic hydroxyl groups, [88] rendering a pHswitchable surface with an isoelectric point of ≈4.5. [47,89] Based on this, pH-responsive PDA was used for the adsorption of charged molecules. [90] Below the isoelectric point the PDA surface charge becomes positive, while DNA is negatively charged above pH 2 due to the phosphate backbone ( Figure 4A).…”
Section: Low Ph-assisted Dna Adsorptionmentioning
confidence: 99%
See 3 more Smart Citations